Falling down a flight of stairs: The impact of age and intoxication on injury pattern and severity. (July 2018) - Chatha, Hridesh; Sammy, Ian; Hickey, Michael; Sattout, Abdo; Hollingsworth, John
Background: Falling down a flight of stairs is a common injury mechanism in major trauma patients, but little research has been undertaken into the impact of age and alcohol intoxication on the injury patterns of these patients. The aim of this study was to compare the impact of age and alcohol intoxication on injury pattern and severity in patients who fell down a flight of stairs. Methods: This was a retrospective observational study of prospectively collected trauma registry data from a major trauma centre in the United Kingdom comparing older and younger adult patients admitted to the Emergency Department following a fall down a flight of stairs between July 2012 and March 2015. Results: Older patients were more likely to suffer injuries to all body regions and sustained more severe injuries to the spine; they were also more likely to suffer polytrauma (23.6% versus 10.6%; p < 0.001). Intoxicated patients were more likely to suffer injuries to the head and neck (42.9% versus 30.5%; p = 0.006) and were significantly younger than sober patients (53 versus 69 years; p < 0.001). Conclusion: Older patients who fall down a flight of stairs are significantly different from their younger counterparts, with a different injury pattern and a greater likelihood of polytrauma. In addition, alcohol intoxication also affects injury pattern in people who have fallen down a flight of stairs, increasing the risk of traumatic brain injury. Both age and intoxication should be considered when managing these patients.